Implementation of Religious Moderation Values in Madrasah Aliyah Darun Najah Malang - Awawina, Elena Kamilia; Zulfah, Machnunah Ani (JoEMS (Journal of Education and Management Studies), 2024)
This research began with the researcher's interest in the application of religious moderation values in the Darun Najah Ngijo Madrasah Aliyah Karangploso Malang environment. Therefore, the problems examined in writing the final assignment are: 1) How to implement the values of religious moderation in the Madrasah Aliyah Darun Najah Ngijo Karangploso Malang 2) How to implement the values of religious moderation in the Madrasah Aliyah Darun Najah Ngijo Karangploso Malang environment. 3) How to evaluate the implementation of religious moderation values within Madrasah Aliyah Darun Najah. To answer this problem, researchers used qualitative research methods to obtain data. Researchers used data collection techniques with observation, interviews and documentation as complementary research aids. Religious moderation as a perspective can be a solution for mutual openness and mutual acceptance of differences between regions, ethnicities, races and cultures as well as religion, one of which is through additional learning of Ahlussunnah Waljamaah (ASWAJA) education in its subjects. The results of this research can be concluded that the implementation of religious moderation values at Madrasah Aliyah Darun Najah has been running and has been implemented smoothly and well because there are also many factors that support students to better understand and apply religious moderation in their daily lives in the environment school.